Experimental study on flexural mechanical properties of steel fiber reinforced alkali-activated slag concrete beams - Yuan, Xiaohui; Huo, Ruijin; Zhang, Xin (Frontiers in Physics, 2024)
As an environmentally friendly alternative to ordinary concrete, slag concrete is subject to limitations such as drying shrinkage and micro-cracking during its promotion and application. In order to address these challenges, steel fibers, known for their excellent tensile, shear, crack-resistance, and toughness properties, have been introduced to enhance the ductility of alkali-activated slag concrete. This study utilized steel fiber content as a variable and produced eight steel fiber-reinforced alkali-activated slag concrete beams to investigate their flexural mechanical properties. By exploring the influence of steel fiber content variation on the mechanical behavior of alkali-activated slag concrete beams and conducting validation through finite element analysis, the study unveiled the impact of steel fibers on the performance of alkali-activated slag concrete beams. The research findings demonstrate a significant enhancement in the flexural mechanical properties of alkali-activated slag concrete beams with the addition of steel fibers, leading to a reduction in surface cracking and an improvement in the durability of the elements. The outcomes of this study hold crucial theoretical implications for the widespread application of steel fiber-reinforced alkali-activated slag concrete.